Proulx, Donald. An analysis of early cultural sequence in the Nepeña Valley. Perú. Research Report Number 25. Department of Anthropology, University of Massachussets. Amherst, 1985. 359 pp., 6 mapas, 4 cuadros, 24 figuras, 18 láminas. Bibliografía. - Román, Alicia J. (1983)
Fil: Román, Alicia J.. Universidad Nacional de Cuyo